SPATIAL ANALYSIS OF LAND CARRYING CAPACITY AND RESIDENTIAL GROWTH IN SIRIMAU DISTRICT, MALUKU PROVINCE, INDONESIA - Lasaiba, Mohammad Amin (Universitas Negeri Surabaya, 2024)
Population growth and urbanization pose challenges in maintaining sufficient land-carrying capacity. This research analyzes land carrying capacity and urban development in Sirimau District, Ambon City. Direct observation and document collection are used to collect data. A quantitative descriptive approach and spatial analysis with overlays of relevant parameters are used in data analysis. The results show that the most significant growth occurs in Batu Merah Village. Land carrying capacity calculations reveal an average decrease in residential land carrying capacity. In 2022, Ahusen Village, Rijali Village, and Galala Village recorded a decline in land-carrying capacity below 1, indicating that these areas can no longer accommodate the remaining population, which suggests that population pressure and unchecked urban growth negatively impact land-carrying capacity. Sustainable management measures, such as prudent urban spatial planning, protection of green areas, and appropriate infrastructure development, must be implemented.